Opinions of Teachers and Administrators Towards the Implementation of Teacher Performance Management Applications at Public and Private High Schools (Ankara Sample) - Bozkurt Bostancı, Aynur; Yolcu, Hüseyin; Şap, Hatice (Elsevier BV, 2011)
This research has been conducted to detect the opinions of teachers and administrators towards the implementations of teacher performance management applications at public and private high schools. In the study, it has been examined that whether opinions of teachers and administrators towards the implementation of teacher performance management applications at public and private high schools differ according to school type, title and of teachers at each school and education level. 74 administrators and 423 teachers working at either public or private schools in Ankara participated in the research. Arithmetical average, t test and two-factor variance analysis techniques have been used in data analyzing. According to results of the study, opinions of teachers and administrators towards the implementation of teacher performance management applications at public and private high schools differ according to school type and task. When the mutual effect of school type and task variables are examined together, it has been viewed that the mutual effect has not is not meaningful about the perceptions of implementation level. Whilst perceptions of public high school teachers’ of performance management applications change within their own school types, it does not differ in view of private high schools.
Keywords: 4. Education